Interface damage and fracture mechanisms of a ceramic/polymer interface based on atomic-scale simulations. Issue 48 (5th December 2022) - Hu, Linhui; Wang, Shuai; Liang, Lihong
Abstract : Interface strength and fracture energy of PP/SiO2 were simulated by developing a MD model, the corresponding interface damage process was characterized quantitatively, and the effect of tensile speed was revealed. Abstract : The performance of ceramic/polymer composite materials is significantly affected by their internal interfaces. To reveal the intrinsic interface fracturing mechanism of ceramic/polymer interfaces, an interfacial model composed of SiO2 and polypropylene (PP) is investigated using the molecular dynamics method. The interface damage is quantified by the increase in the interface free volume and deformation of a single PP chain. As stretching speeds increase, the free volume and outflowing atoms of PP chains decrease with the same interfacial displacement, which results in the increase of the interface strength and fracture energy. At low stretching speeds, the interface damage mechanism is determined by a competition between attractions of the PP single chains from SiO2 and PP. In contrast, at higher stretching speeds, the interface fracture is more brittle and the interface strength and fracture energy are both higher owing to the smaller cavity ratio. The results of this study contribute to an in depth understanding of the fracture mechanism of ceramic/polymer interfaces in many systems.